Trade openness, technological spillovers, and income inequality in Latin America: A panel data analysis (2000–2022) - CHEHAOUI, Lidia; BOUKLIA, Nawel; TOUITOU, Mohammed (The International tax journal, 2025)
This paper investigates the relationship between trade openness, technological spillovers, and income inequality in Latin America using panel data from 15 countries over the period 2000–2022. It explores how globalization dynamics—specifically trade integration and R&D imports—interact with human capital and institutional quality to shape inequality outcomes. Employing fixed effects and system GMM estimations, the study finds that trade openness tends to increase income inequality in countries with weak educational systems, while technology diffusion may reduce inequality when governance institutions are strong. Interaction effects highlight the critical role of national absorptive capacities in mediating globalization’s distributive impacts. Robustness checks support the reliability of these results. A comparative lens incorporating MENA, East Asia, and Eastern Europe further underscores the importance of policy sequencing, institutional scaffolding, and inclusive investment. The paper concludes with region-specific policy recommendations to enhance equity through education, innovation, and institutional reform.